Degradation mechanism of coal pillars in an underground coal gasification environment: Bearing capacity, pyrolysis behaviour and pore structure - Jian Li; Jinwen Bai; Guorui Feng; Erol Yilmaz; Yanna Han; Zhe Wang; Shanyong Wang; Guowei Wu (International Journal of Mining Science and Technology)
Coal pillars are critical supporting structures between underground coal gasification gasifiers. Its bearing capacity and structural stability are severely threatened by high-temperature environments. To elucidate the high-temperature deterioration mechanism of coal pillars at multiple scales, coal strength features as a function of temperature were investigated via uniaxial compression and acoustic emission equipment. The pyrolysis reaction process and microstructure evolution were characterized via X-ray diffractometer (XRD), scanning electron microscope (SEM), thermogravimetric (TG), Fourier transform infrared spectroscopy (FTIR), and computed tomography (CT) tests. Experimental results reveal a critical temperature threshold of 500 °C for severe degradation of the coal bearing capacity. Specifically, both the strength and elastic modulus exhibit accelerated degradation above this temperature, with maximum reductions of 45.53% and 61.34%, respectively. Above 500 °C, coal essentially undergoes a pyrolysis reaction under N2 and CO2 atmospheres. High temperatures decrease the quantity of O2-based functional groups, growing aromaticity and the degree of graphitization. These changes induce dislocation and slip inside the coal crystal nucleus and then lead to deformation of the coal molecular structural units and strain energy generation. This process results in a great increase in porosity. Consequently, the stress deformation of coal increases, transforming the type of failure from brittle to ductile failure. These findings are expected to provide scientific support for UCG rock strata control.